FAIR PRICE OF STOCK USING PRICE EARNING RATIO AND PRICE TO BOOK VALUE IN INVESMENT SERVICE COMPANIES - Hadi Satria Ganefi; Yasir Maulana; Wachjuni Wachjuni (INDONESIAN JOURNAL OF BUSINESS AND ECONOMICS, 2026)
Investment is a current sacrifice made by investors with the aim of achieving future profits. One instrument investors utilize in investing is stocks, which offer high returns accompanied by high risks. Therefore, to minimize risk and maximize returns, investors require adequate information and accurate analysis of the stocks they choose. This study aims to analyze the fairness of stock prices of Investment Services sub-sector companies listed on the Indonesia Stock Exchange during the 2024 period using fundamental analysis with the Price Earnings Ratio (PER) and Price to Book Value (PBV) methods. Purposive sampling was used as a sampling technique, and four companies were selected. The results showed that, based on fundamental analysis using the PER and PBV methods, two companies were overvalued and one company was undervalued. However, inconsistent results were found within one company. This study provides information that can be used as a basis for consideration by investors in making investment decisions, both to buy and sell shares, especially in the investment services sector.